Rede bancária e interações espaciais: a dinâmica da Região Imediata de Currais Novos (RN) no período técnico-científico-informacional - Silva, Eulália Jéssica Medeiros (2021)
At the current stage of the internationalization of capital, called the technicalscientific-informational period, the production of space is increasingly characterized by the uses of the technical, science, information, consumption and finance variables. Such variables are key to understanding the production of space in this period, due to the fact that they are trivialized in social and geographic terms. Thus, in this work we study the dynamics of the Immediate Region of Currais Novos (RN) according to the banking network. This region of Rio Grande do Norte – defined by the IBGE (2017) – is composed of nine municipalities – Acari, Bodó, Carnaúba dos Dantas, Cerro Corá, Currais Novos, Florânia, Lagoa Nova, São Vicente and Tenente Laurentino Cruz –, of which eight have municipal headquarters defined – in the context of the urban network of Rio Grande do Norte – as local city, while Currais Novos presents itself as an urban center of regional prominence, as it has the most complex market. Between 1954 and 2012, the banking network was expanded in this region, with the installation of bank branches in Currais Novos and also in local cities. However, in 2016, crimes were committed against existing bank branches in the region, and since then, the expansion of the banking network has been redefined, due to the fact that, in local cities, bank branches have been transformed into service stations and have expanded the provision of banking correspondent services. Thus, in 2020, there were bank branches only in Currais Novos, which gave the banking network a low density and a strong hierarchy in the urban network. Considering this problem, the objective of this work is to analyze the dynamics of the Currais Novos region according to the banking network, paying attention to the socioeconomic dynamics of local centers and the regional backcountry center, to the expansion and retraction of the banking network and to spatial interactions developed in the region. Through bibliographic research, statistical data research and field research, we have systematized the work in three chapters: in the first, we apprehended the socioeconomic dynamics of the cities in the Currais Novos region, in the context of the economic restructuring of Seridó Potiguar region, underlining the process urbanization; in the second, we analyze the process of expansion and redefinition of the banking network in the region in question, considering the capillarity of existing banks in the space; and, finally, we analyze the contribution of this banking network to spatial interactions in the region. We concluded that the dynamics of the region according to the banking network is unequal, with the privilege of the city that concentrates the largest flows of people, capital and goods, while the other cities find less complex bank landmarks, which are implemented focusing on the possibility of banking institutions profit more from lower investment.